Variasi Pemaknaan Penganut Hindu di Bali Terhadap Mitos Gangguan Mental pada Cerpen Buduh Karya Ida Bagus Widiasa Keniten - Sugiharta, I Putu Suweka Oka (Metta : Jurnal Ilmu Multidisiplin, 2025)
Mental disorders are an obstacle to human resource development. Various efforts can be made to overcome mental disorders, including by utilizing the meaning of myths. Unfortunately, some people understand myths incorrectly so that they are unable to utilize them appropriately. The purpose of this study is to obtain an overview of the variation of Balinese Hindus' interpretation of the myth of mental disorder in the “Buduh” short story by Ida Bagus Widiasa Keniten. This research was conducted by following a qualitative descriptive procedure; the data analyzed are non-numerical. Specifically, content analysis of the literary works studied was carried out so as to obtain results in accordance with the theme of the study. The findings of this study reveal that the myths in the “Buduh” short story are in line with the teachings of Hinduism. It is also considered that the holistic aspect of mental health must touch the physical, mental, and spiritual dimensions. The incompleteness of interpreting mental disorders will lead to incomplete treatment. In the “Buduh” short story, the author presents myths of mental disorders ranging from supra-rational to logical levels. The supra-rational element is spiritual, supernatural, and mystical. Supra-rational meanings include belief in repeated births (punarbhava) and black magic. At the supra-rational level, it is very difficult for humans to gain a logical understanding of the causes of mental disorders. Nevertheless, people who interpret it are still directed towards nobility of character. Meanwhile, at the logical level, the causes of mental disorders can be traced with common sense. Ultimately, both supra-rational and logical myths actually stimulate humans to be able to behave wisely as both domestic and external parties. When this happens, a complete human relationship will soon be realized.